Blocking Epidermal Growth Factor Receptor Signaling in HTR-8/SVneo First Trimester Trophoblast Cells Results in Dephosphorylation of PKBα/AKT and Induces Apoptosis - J. Bolnick; L. Albitar; L. L. Laidler; R. Abdullah; K. K. Leslie (Obstetrics and Gynecology International)
We identified a major peptide signaling target of EGF/EGFR pathway and explored the consequences of blocking or activating this pathway in the first trimester extravillous trophoblast cells, HTR-8/SVneo. A global analysis of protein phosphorylation was undertaken using novel technology (Kinexus Kinetworks) that utilizes SDS-polyacrylamide minigel electrophoresis and multi-lane immunoblotting to permit specific and semiquantitative detection of multiple phosphoproteins. Forty-seven protein phosphorylation sites were queried, and the results reported based on relative phosphorylation at each site. EGF- and Iressa-(gefitinib, ZD1839, an inhibitor of EGFR) treated HTR-8/SVneo cells were subjected to immunoblotting and flow cytometry to confirm the phosphoprotein screen and to assess the effects of EGF versus Iressa on cell cycle and apoptosis. EGFR mediates the phosphorylation of important signaling proteins, including PKBα/AKT. This pathway is likely to be central to EGFR-mediated trophoblast survival. Furthermore, EGF treatment induces proliferation and inhibits apoptosis, while Iressa induces apoptosis.